Concept and activities of the financial services regulation coordinating committee (FSRCC) in Nigeria 1994-1996 - Ebhodaghe, john u. (Abuja, Nigeria Nigeria Deposit Insurance Corporation, 1997)
The establishment of FSRCC was as a result of the advent of an economic structural adjustment programme which led to financial deregulation with an unprecedented increase in the number and variety of licensed financial institutions with differing missions, modi operandi and regulation / supervision.
Includes appendix and index (176-178)
nmn, 11/08/16
Loan
Keywords: Financial services regulation